0330 A Study of Radiographic Abnormalities in Minnesota Taconite Workers. (23rd June 2014) - Mandel, Jeff; Lambert, Christine; Alexander, Bruce; MacLehose, Richard; Ramachandran, Gurumurthy
Abstract : Objectives: A limited number of studies have been conducted in the taconite industry, typically without detailed exe posure information. We assessed occupational exposure to elongate mineral particles (EMP) in association with chest x-ray findings in a cross-sectional screening of 1188 current and former taconite workers. Method: Exposure was determined by a combination of some 1300 onsite measures taken by researchers and historical measures taken by mining companies. The NIOSH 7400 measurement method (PCM) was used to count EMP. Twenty-eight similarly exposed groupings (SEG) were developed and contained all jobs. Each SEG had multiple EMP measures as an anchoring point for historical exposure estimates. Work histories were standardised, mapped to SEGs and used to estimate exposures for each worker in each SEG. Chest x-rays were obtained using ILO methods, with two independent radiologists. Prevalence odds ratios were estimated by logistic regression for work duration and cumulative EMP exposure, adjusting for age, gender, BMI and occupations with high potential for asbestos. Results: Pleural findings occurred in 16.8% by consensus. Abnormalities were associated with duration of employment in the taconite industry for those working 21 years or more (OR=1.59, 95% CI=1.06–2.40). Pleural abnormalities were also associted with cumulative exposure to EMP for those cumulatively exposed to 1.16 EMP/cc-years or more (OR=1.93, 95% CI=1.32–2.83). Associations between parenchymal abnormalities and exposure were not observed. Conclusions: This study suggests that pleural abnormalities are related to duration of employment and to EMP exposure in taconite miners. Due to the measurement method, the specific type of EMP could not be described further.